Mapping for Reconnection: Place Name Documentation and the Atlas of Kanyen'kehá:ka Space - Ingram, Rebekah R.; Horn-Miller, Kahente (KULA)

(untitled) (University of Victoria Libraries, 2024)
Indigenous place names contain knowledge of the landscape and encode unique perceptions of landscapes with which Indigenous Peoples have interacted for hundreds, often thousands, of years. However, many Indigenous place names have been lost as a result of colonization. Furthermore, many of these have been replaced with colonial place names, and their loss contributes to overall language attrition. In turn, the loss of language makes it difficult, or even impossible, to understand the concepts embedded within Indigenous place names that do remain in use. The documentation and conservation of place names is thus an important aspect of Indigenous language preservation and revitalization that can help facilitate reconnection with the language and the land. This paper outlines the Atlas of Kanyen'kehá:ka Space digital atlas project, an initiative that uses digital mapping to aid in the documentation and revitalization of the Kanyen'kéha (Mohawk) language through community participatory mapping of Kanyen'kéha place names and landscape-related language. It describes the initial stages of the Atlas of Kanyen'kehá:ka Space project, including its theoretical framework, the O'nonna model, and its community-based participatory methodology for digital mapping. It reports on a series of mapping workshops within three Kanyen'kehá:ka communities and shares initial findings and future directions for the project.